Answer:
(x+3)²-11=0
Step-by-step explanation:
0=9(x2+6x)-18
0= 9x² +54x-18
0= 9( x²+6x-2) taking 9 common
0= x² +6x-2 (breaking the mid term to find the second element of the square
0 = (x)² +2(x)(3) +(3)² -2 -9 adding and subtracting the second element
0= (x+3)² -11 summing up
Answer:
4x-8>-4
Step-by-step explanation:
2-(2x-4)>-4
2- times (2x) = 4x
2- times (-4) = -8
answer is
4x-8>-4
Answer: 1.0/5. 7.
Step-by-step explanation:
50
(e= 10 to the power of)
6.6e-2/3.3e-4= 3.3e4/6.6e2=0.5e2= 0.5x10^2=50